Toward the automation of a QoS-driven SLA establishment in the Cloud. Issue 3 (September 2016) - Boukadi, Khouloud; Grati, Rima; Ben-Abdallah, Hanêne
Abstract Composite software as a service (SaaS)-based SOA offers opportunities for enterprises to offer value-added services. The cornerstone for such a business is service level agreements between Cloud customers and Cloud providers. In spite of the hype surrounding composite SaaS, standardized methods that enable a reliable management of service level agreements starting from the SLA derivation from the customer requirements to the SLA establishment between the two stockholders are still missing. To overcome such a drawback, we propose a method for SLA establishment guided by QoS for composite SaaS. Our method provides: (1) a requirement specification language for the Cloud customer to define the composition schemas of the requested services along with its QoS constraints; (2) a Cloud provider offer specification language and method to help in identifying the services and resources that satisfy the customer requirements; and (3) an SLA document definition language and method to specify a deployable composite SaaS on the Cloud. Our approach for SLA establishment embraces model-driven architecture principles to automate the SLA document generation from the customer requirements document. The automation is handled through model transformations along with enrichment algorithms to ensure the generation of complete SLA documents.